Studi Komparatif Sistem Pendidikan Dasar di Finlandia dan Indonesia: Penguatan Learning Community - Putri Deby Ramona; Komarudin Sassi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Directly or indirectly, the policy of the independent learning curriculum concept adopted in the education system in Indonesia is more or less rooted in the policy that applies in Finland. Because the education system in Finland gives teachers and lecturers the freedom to innovate, be independent, active, creative and innovative in learning activities. Through comparative descriptive analysis, this research seeks to compare the basic education systems in Indonesia and Finland. The data source is primary data obtained through observations of early grade children aged 7-8 years. Meanwhile, secondary data uses literature reviews and video analysis of the implementation of education system activities from the two countries. Then the data was analyzed using descriptive analysis methods. The research results showed that the Finnish government provides very high support for the provision of various physical and non-physical infrastructure such as; school facilities, teacher qualifications, equal and equitable education for all citizens as well as strengthening learning communities. On the other hand, Indonesia also continues to improve in meeting the various needs for educational facilities evenly in various remote rural areas in order to realize the dream of a Golden Indonesia in 2045.